The role of high-sensitivity C-reactive protein serum levels in the prognosis for patients with stroke: a meta-analysis - Chen, Liuting; Wang, Min; Yang, Chanrui; Wang, Yefei; Hou, Bonan (Frontiers in Neurology, 2023)
Background: The impact of high-sensitivity C-reactive protein (hs-CRP) as a biomarker of inflammation on the prognosis of stroke patients remains controversial, this study was conducted to evaluate the prognostic value of hs-CRP levels for patients with stroke. Methods: PubMed, Web of Science, Embase, and Cochrane Library databases were searched from inception to October 28, 2022. Outcome measures were all-cause mortality, recurrent stroke, and poor prognosis. The relationship between the highest versus lowest levels of hs-CRP or per unit increment and outcomes as measured by risk ratio (RR) and corresponding 95% confidence intervals (CI) Results: A total of 39 articles were eligible for meta-analysis. High hs-CRP levels at admission were associated with mortality among patients with acute ischemic stroke (AIS) (RR=3.84, 95% CI [2.41 6.111]; P<0.001), risk of recurrent stroke (RR=1.88, 95%CI [1.41 2.52]; P<0.001), and poor prognosis (RR=1.77, 95% CI [1.59 1.97]; P<0.001). The risk ratios for the association of per unit increase in hs-CRP levels with mortality, risk of recurrent stroke, and poor prognosis were as follows, respectively: 1.42 (95% CI [1.19-1.69]; P<0.001), 1.03 (95% CI [1.01-1.04]; P=0.003), and 1.27 (95% CI [1.10-1.47]; P=0.001). For hemorrhagic stroke (HS), the risk ratios (RR) for the highest versus the lowest (reference) category of hsCRP or per unit increment to all-cause mortality were 4.36 (95% CI 1.38-13.73; P=0.012) and 1.03 (95% CI 0.98-1.08; P=0.238). Conclusion: Hs-CRP levels are strongly associated with mortality, risk of stroke recurrence and poor prognosis in stroke patients. Therefore, hs-CRP levels may contribute to the prognosis prediction of these patients.